IMPLEMENTATION DECISION SUPPORT SYSTEM DETERMINING ELIGIBILITY OF DIRECT CASH AID RECIPIENT COMMUNITIES - Aprizal, Aprizal; Jasri, Jasri (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Pulau Kopung Sentajo Village Government in determining communities recipients of Direct Cash Assistance (BLT) has not used a computerized system so that in decision making errors will often occur in the suitability criteria for potential BLT recipients. So things like this will increase the possibility that poor or underprivileged people will lose out to people who live better lives and also take a lot of time because they still use manual systems. In terms of the report produced, it does not display the criteria for potential recipients clearly and in detail. In solving the problem, a decision support system will be used using the simple additive weighting method. So this research produces a computerized system to support decision making that determines people's suitability as recipients of direct cash assistance. With this computerized system, it will make it easier to determine the eligibility of people receiving Direct Cash Assistance and produce effective reports with calculations that comply with existing criteria. By implementing this computerized decision support system, 7 people are recommended who are eligible to receive direct cash assistance with the highest score of 2,875 and the lowest score of 2,750 so that these results can assist the village head in determining the community's suitability as recipients of direct cash assistance. Keywords: assistance; BLT; SAW; FMADM; Abstrak: Pemerintah Desa Pulau Kopung Sentajo dalam menentukan masyarakat sebagai penerima Bantuan Langsung Tunai (BLT) belum menggunakan sistem yang terkomputerisasi sehingga dalam pengambilan keputusan akan sering terjadi kesalahan dalam perbandingan kriteria kesesuaian calon penerima BLT. Sehingga hal seperti ini akan memperbesar kemungkinan masyarakat miskin atau kurang mampu akan kalah dengan masyarakat yang kehidupannya lebih baik dan juga memakan banyak waktu karena masih menggunakan sistem manual. Dari segi laporan yang dihasilkan, tidak menampilkan kriteria calon penerima secara jelas dan rinci. Dalam penyelesaian masalah akan digunakan sistem penunjang keputusan dengan metode simple additive weighting. Maka dengan penelitian ini menghasilkan sistem yang terkomputerisasi untuk mendukung pengambilan keputusan menentukan kelayakan masyarakat sebagai penerima bantuan langsung tunai. Dengan sistem yang terkomputerisasi ini, maka akan memberikan kemudahan dalam menentukan kelayakan masyarakat penerima Bantuan Langsung Tunai dan menghasilkan laporan yang efektif dengan perhitungan yang sesuai dengan kriteria yang ada. Dengan penerapan sistem pendukung keputusan yang terkomputerisasi ini maka direkomendasikan 7 orang yang layak menerima bantuan langsung tunai dengan skor tertinggi 2,875 dan skor terendah 2,750 sehingga hasil tersebut dapat membantu kepala desa dalam menentukan kelayakan masyarakat sebagai penerima bantuan tunai langsung. Kata Kunci: bantuan; BLT; SAW; FMADM